PATRÓN COMPORTAMENTAL Y CONDUCTAS ESTEREOTIPADAS DE DOS GRUPOS CAUTIVOS DE ATELES FUSCICEPS ROBUSTUS EN COLOMBIA - Cardona López, Doris Ximena; Laboratorio de Ecología de Poblaciones y Comunidades. Unidad de Ecología y Sistemática (UNESIS), Departamento de Biología, Facultad de Ciencias, Pontificia Universidad Javeriana, Bogotá (2004)
The study describes the behavior patterns and stereotyped conduct of two groups of Ateles fusciceps robustus, living in cages or being captive in an  island, respectively, in two different zoological parks (Santacruz and Jaime Duque) located near Bogotá, Colombia. Individuals of the same sex and age had a similar behavior; the same was true for females with infants. The younger individuals showed a larger behavior repertory. Both groups showed more stereotypes before their meal was served and when exposed to loud sounds, such stereotypes being more frequent in individuals enclosed in cages. In order to improve the well-being of the individuals and to reduce their stress levels, environmental enrichment strategies were proposed.